ANALISIS PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MUGHNI FACTORY INDONESIA DI TANGERANG SELATAN - Akka Latifah Jusdienar (Sekolah Tinggi Manajemen IMMI, 2022)
The purpose of this study was to determine how much influence work discipline has on employee performance at PT. Mughi Factory Indonesian. The population of this research is all employees and employees at PT. Mugni Factory Indonesia, which has 30 employees. While the sampling method used is a quantitative method, so the number of samples is determined as many as 30 people. To obtain the required data, the data collection method used is a questionnaire or questionnaire.The results show that: 1) The influence of Work Discipline (X) has a significant effect on Employee Performance (Y), because the tcount value for the X variable (Work Discipline) is 8,156, while the ttable value for n = 30 is 2,042. So 8,156 2,042, it can be concluded that partially the Work Discipline variable (X) has an effect on Employee Performance (Y). 2) In the Summary Model, it is proven that the R Square value of 0.704 means that Work Discipline has an influence of 70.4% on Employee Performance while the remaining 29.6% has an effect on other factors not examined by the authors in this study.Keywords: Work Discipline and Employee Performance.